Beyond binary thinking: Making sense of modernity as a historical phenomenon - Goga, Safiyya (PINS-Psychology in Society, 2015)
Alexander, Jeffrey, C (2013) The dark side of modernity. Cambridge: Polity Press. ISBN 978-0-7456-4822-4 pbk. Pages viii + 187